2022
DOI: 10.1111/jfpp.16983
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan and acerola ( Malpighia emarginata ) fruit based active coating can control the melanosis of refrigerated shrimps ( Litopenaeus vannamei )

Abstract: Sodium metabisulfite is a chemical compound used to reduce melanosis of shrimps. However, this chemical compound has been associated with several human diseases and negative environmental impacts. Therefore, this study aimed to develop, characterize, and apply a coating and film based on natural and not toxic compounds. A chitosan‐based coating and a film containing acerola fruit powder were developed and characterized for various physicochemical and microstructural properties. The presence of acerola altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The variation in the contact angle as a function of time (Figure 3) indicated that the increase in the number of printed layers promoted a reduction in the contact angle in relation to the control OF (without GPEE printing). The contact angle values of chitosanbased films were greater than 90 • C, indicating a hydrophobic character [79,80]. However, the incorporation of GPEE caused a reduction in the contact angle, indicating greater surface hydrophilicity.…”
Section: Contact Anglementioning
confidence: 96%
“…The variation in the contact angle as a function of time (Figure 3) indicated that the increase in the number of printed layers promoted a reduction in the contact angle in relation to the control OF (without GPEE printing). The contact angle values of chitosanbased films were greater than 90 • C, indicating a hydrophobic character [79,80]. However, the incorporation of GPEE caused a reduction in the contact angle, indicating greater surface hydrophilicity.…”
Section: Contact Anglementioning
confidence: 96%